Can Sukuk Become a Primadonna In Indonesia? Judging From The Development of Sukuk In Several Countries - Zul Hendri (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2018)
The purpose of this study was to find out how the history of sukuk and the development of sukuk growth in various countries. the development of sukuk can also be seen from the structure of the sukuk that is currently developing. The research method used by the author is the study of literature. The author collects scholarly journals and financial reports from various sources. This paper aims to find out how sukuk develop using the right sukuk structure so that sukuk can be an alternative in improving the country's economy. Research limitations/implications – The data analysis was restricted to two countries, but this could be extended. Alternative pricing benchmarks were suggested for sovereign sukuk but not for corporate sukuk. Ministries of Finance and Central Banks of Muslim countries should review their debt financing policies and explore the potential of sovereign sukuk. Little has been written previously on the use of musharakah partnership contracts for sukuk, and pricing issues have not hitherto been systematically investigated.